Efektivitas Penggunaan Transaksi Digital Dalam Menunjang Kinerja Bisnis - Agit, Alamsyah; Wildayanti, Wildayanti; Oktavianty, Oktavianty (Prodi Manajemen S1 dan D3 Keuangan & Perbankan, 2024)
The efficiency of digital transactions contributes significantly to the enhancement of business performance. Digital transactions offer a variety of advantages, including convenience, security, and accessibility, which can increase business efficiency and productivity, expand market reach, and boost consumer interactions. However, there are obstacles to using this technology, particularly for business proprietors who are unfamiliar with it. Using qualitative methods and a literature review approach, this research utilizes data and empirical research as data sources, which are then processed using deductive reasoning to obtain results and draw conclusions pertinent to the research topics. According to the findings of this study, digital transactions and other forms of technology support business performance well, but there are obstacles that prevent technological adaptation from being evenly distributed. Therefore, commitment, education, digital awareness, evaluation, increased security, stringent regulations, and cooperation are required from all parties. It is necessary to conduct additional research in order to comprehend the obstacles and difficulties encountered by traditional businesses in adopting digital technologies and creating new business opportunities.